2004
DOI: 10.1080/0042098042000226939
|View full text |Cite
|
Sign up to set email alerts
|

Separate Spaces, Separate Outcomes? Neighbourhood Impacts on Minorities in Germany

Abstract: In both the German and US literature on ethnic neighbourhoods, there is considerable debate as to whether living amongst co-ethnics hinders or furthers the integration process for immigrants. Using the detailed data on immigrant integration in the German Socio-economic Panel in combination with zip-code-level data on minority concentration and neighbourhood income levels, the research tests the extent to which ethnic neighbourhoods are economically, socially and/or culturally isolated spaces in Germany. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 24 publications
3
56
1
3
Order By: Relevance
“…Vervoort et al 2010), there are also studies that question the dependence of inter-ethnic contacts on ethnic residential segregation (e.g. Drever 2004) are troubling from the perspective of this approach. Well in line are findings that support the importance of host-country language skills for migrants' interethnic contacts to natives (e.g.…”
Section: Proximity Assortative and Relational Mechanismsmentioning
confidence: 99%
“…Vervoort et al 2010), there are also studies that question the dependence of inter-ethnic contacts on ethnic residential segregation (e.g. Drever 2004) are troubling from the perspective of this approach. Well in line are findings that support the importance of host-country language skills for migrants' interethnic contacts to natives (e.g.…”
Section: Proximity Assortative and Relational Mechanismsmentioning
confidence: 99%
“…The 25% cutoff was chosen because according to the SOEP, a majority of persons living in zip code areas that are 25% or more non-citizen feel they are living in an area with 'many foreigners' (see Drever 2004). Zip code areas in Germany's largest cities contain an average of 17,700 persons and are similar in size to U.S. zip codes, which are commonly used in neighborhood research (see Because immigrants on average earn less than Germans (see Münz et al 1997) one might expect average incomes of Germans in the neighborhoods where immigrants are concentrated to be lower as well.…”
Section: Ethnic Neighborhoodsmentioning
confidence: 99%
“…shown that immigrants living in ethnic neighborhoods tend to be concentrated in poorer-quality housing (Drever 2004). Might that be true for non-immigrant Germans as well?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De eneste indikationer er, at beboerne i de multietniske boligområder sjaeldnere opnår kontakten med danskerne via selve boligområdet, og at der er faerre af dem, der udelukkende bruger danske medier. I en mere omfattende tysk undersøgelse (Drever 2004) findes tilsvarende konklusioner -at indvandrere i multietniske boligområder ikke er dårligere til tysk og mere kulturelt isoleret end indvandrere udenfor.…”
unclassified